KAJIAN SEJARAH TARI ZAPIN ARAB DI KOTA PONTIANAK - Syarifah Meyfira Nazlia Fuaddah; Ismunandar Yahya; Winda Istiandini (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2020)
AbstractThe background of this study is the interest of researchers in the arts that are influenced by Islam and art that has long faded among the Pontianak community as well as researcher’s interest in the uniqueness of dance in Pontianak. One of the tradition is  Zapin Arab dance, so researchers wanted to explain and told the detail  ofthe history of Zapin Arab Dance and the development of Zapin Arab dance in Pontianak.  The goal was to find out about the history of Zapin Arabic by documenting in writing form and supported by photographs of Zapin Arab performance, so that the history of Zapin Arabic dance could be known by the people of Pontianak City and the society. The method used is a historical method, with qualitative research.  The research approach used is a multidisciplinary. The data sources in this study are primary and secondary sources, where primary data were obtained from five sources who studied the history of Zapin Arabic dance trips and secondary sources were obtained from books sources that relating to Zapin dance.  Data collection techniques consist of book study, observation, interviews, and documentation.  The technique of testing validity data uses triangulation of sources and techniques. The history of Zapin Arabic dance comes from the word "Zafn" which means the movement of the feet.  It was brought by the people of Hadramaut Yemen as art which was introduced together with the introduction of Islam in the 6th century. It is estimated that Zapin began to enter Indonesia in the 13th century until the 18th century brought by Yemeni missionaries and Yemeni traders to spread the Islamic religion and attract customers.  This Zapin dance began to enter the city of Pontianak to coinciding with the time after the establishment of the city of Pontianak, which was the first sultanate of Sultan Syarif Abdurrahman Al-qadrie in 1771 AD                    Keywords: Development, History,  Zapin Arabic Dance